Jātīẏa yātrā uṯsaba, 1978-1979 (Bāṃlādeśa Śilpakalā Ekāḍemī, 1979)
Souvenir issued on the occasion of the national folk opera festival, organized by the Bangladesh Shilpakala Academy; comprises articles on the form, nature, and history of the Bengali open air theater, festival program, and list of opera parties of Bangladesh.